2019
DOI: 10.1111/dth.12831
|View full text |Cite
|
Sign up to set email alerts
|

Intramatricial platelet‐rich plasma therapy: A novel treatment modality in refractory nail disorders

Abstract: Two patients, one with nail lichen striatus and second with idiopathic trachyonychia were treated with intramatriceal injections of platelet‐rich plasma. A total of 0.1 ml of the plasma solution was injected into the matrix of the involved nails at three weekly intervals. Follow‐up was done at each sitting and thereafter at 16 and 20 weeks. Assessment was done both photographically and by dermoscopy. Case 1 showed marked improvement within 3 weeks and Case 2 showed improvement within 6 weeks. No relapses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…One study reported the significant benefit of three-weekly intramatricial PRP injections in refractory nail disorders like nail lichen striatus and idiopathic trachyonychia. [ 56 ] While the former responded in 3 weeks, the latter case showed significant improvement in 6 weeks of therapy. No relapses were seen during follow-up for 16 and 20 weeks, respectively.…”
Section: Prp In Dermatologymentioning
confidence: 99%
“…One study reported the significant benefit of three-weekly intramatricial PRP injections in refractory nail disorders like nail lichen striatus and idiopathic trachyonychia. [ 56 ] While the former responded in 3 weeks, the latter case showed significant improvement in 6 weeks of therapy. No relapses were seen during follow-up for 16 and 20 weeks, respectively.…”
Section: Prp In Dermatologymentioning
confidence: 99%
“…The authors stated, "…after 2 months he was started on intramatricial platelet rich plasma (PRP) therapy, after discussing and exhausting all other management options." 1 We request them to elaborate on what all treatment options (other than TCS monotherapy and IM-TA shots) were offered, attempted, and failed in the next 2 months, prompting them to try IM-PRP therapy. Despite therapeutic options for NLS being limited, the modest-to-satisfactory efficacy has been documented with pharmacological approaches other than TCS/TCL (with low but definitive evidence), which merited therapeutic trial before an "innovative therapy" with no precedent experience in nail disorders (a factually wrong assertion by the authors vide infra).…”
Section: Sidharth Sonthaliamentioning
confidence: 99%
“…The authors administered IM-PRP as the first treatment for trachyonychia in their second case with past history of single attempt of treatment (some TCS of undisclosed potency applied for only 8 weeks). 1 Substantial evidence supports self-improvement/resolution of idiopathic trachyonychia over time, especially in adults, rendering the physician's approach of counseling, reassurance, and patient and masterly nonintervention as the first-line approach. Furthermore, at least 7 to 8 topical/systemic treatments resulting in significant improvement to complete clearance have been reported, with the highest grade of evidence (significant improvement in 98.6% treated nails in 36 patients) for non-occlusive application of calcipotriol/betamethasone dipropionate ointment OD over the proximal nail folds × 6 months.…”
Section: Oversight Of Ethical Aspects Including Validity Of Informed mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 8 9 10 ] There are reports of use of platelet-rich plasma (PRF) for refractory nail dystrophies with good results. [ 11 ] So we conducted this study to see whether or not combined therapy of intramatricial PRP and triamcinolone is more effective than intramatricial triamcinolone therapy alone in treating refractory nail dystrophy.…”
Section: Introductionmentioning
confidence: 99%